Primary Breast Burkitt Lymphoma. A Case Report of a 16-Year-Old Female with a Rapidly Growing Unilateral Breast Mass - Mitala, Yekosani; Ssenkumba, Brian; Nabulya, Rita; Kitenda, Francis Nsumba; Tumwesigye, Habert; Birungi, Abraham; Chau, Richard Dratu; Mushabe, Branchard; Baker, Nichole; Atwine, Raymond (Cancer Management and Research, 2023)
Introduction: Primary breast Burkitt lymphoma is extremely rare. Commonly endemic Burkitt lymphoma presents with abdominal, jaw, periorbital, or genitourinary mass. Case Presentation: We report a case of a 16-year-old girl with rapidly enlarging left breast swelling associated with evening fevers. This was later confirmed to be stage 1 primary breast Burkitt lymphoma involving the left breast. This represents the first described case of primary breast endemic Burkitt lymphoma in Uganda. She was started on chemotherapy and exhibited an impressive response to the drugs. Conclusion: This case raises awareness of rare sites for endemic Burkitt lymphoma in Uganda. Accurately diagnosing this case was of great importance since it determined the treatment modality (mastectomy or not) which would have an everlasting impact on her life.
Keywords: Primary breast Burkitt lymphoma; Uganda; A case report